Five new species of Disepyris Kieffer, 1905 (Hymenoptera: Bethylidae), with emended generic diagnosis - Lim, Jongok; Azevedo, Celso O. (Zootaxa, 2014)
Five new species of Disepyris Kieffer (Hymenoptera: Bethylidae) are described and illustrated: D. kenyaensis Lim & Azevedo, sp. nov. (Kenya), D. fessus Lim & Azevedo, sp. nov., D. mongoliaensis Lim & Azevedo, sp. nov., D. prolatatus Lim & Azevedo, sp. nov. (Mongolia), D. niveus Lim & Azevedo, sp. nov. (United Arab Emirates) and the genus is first recorded from Yemen, based on a female of D. guigliae (Benoit). The diagnosis of Disepyris is emended by a combination of following characteristics: head with palpal formula 6:3; ventral surface of antennal flagellomeres III–XI with one pair of parallel basiconic sensillae; clypeus with median lobe distinctly wider than lateral lobe; eyes with sparse, very minute hairs; occipital carina present; mesonotum with notauli weakly carinate, present on anterior half of mesoscutum, median area without transverse foveolate or punctate groove; propodeal spiracle present antero-dorsally on propodeal disc, lateral surface of propodeum strigate; forewing without postmarginal vein, long radial flexion line present, medial flexion line divided into two apical lines. Legs polished without sculpture, appressed pubescence absent; mesotibia with sparse, short spines on apical half; hind basitarsus with one row of comb ventrally.